Addressing a Critical Voice in Clinical Practice: Experiences of Nursing Students, Teachers, and Supervisors-A Qualitative Study - Ingrid Rachel Strand; Unni Knutstad; Anton Havnes; Mette Sagbakken (MDPI AG, 2024)
Aim: Our goal was to explore how power asymmetry manifests within the relationships between students, teachers, and supervisors, and how it influences students' ability for critical reflection. Design: This study has an explorative qualitative design. Methods: Thirty in-depth interviews with nursing students (15), teachers (9), and supervisors (6) were conducted in addition to 16 observations of mid-term assessments during clinical practice. The analysis was conducted using Braun and Clarke's thematic analysis. Results: The students described being a student as a balancing act between humility, conforming to the supervisor's expectations, and speaking their minds. The view expressed by the teachers and supervisors is that training for the nursing profession is closely linked to the students' ability to act independently. Due to the supervisors' hierarchical position, however, students are hesitant to voice any criticism regarding insufficient supervision or unsatisfactory performance of clinical tasks while at the same time being evaluated on their ability to critically reflect on their own and others' clinical performance. This study was prospectively registered with the Norwegian Centre for Research Data on the 15th of August 2017 with the registration number 54821.